Analisis Konseptual tentang Penerapan Teori Probabilitas Lanjut dalam Pengembangan Model Statistik Modern - Hanggoro, Dimas Banu Dwi (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2025)
This study aims to examine the application of advanced probability theory in the development of modern statistical models through a Systematic Literature Review approach to 25 scientific articles published in 2020–2025. This study is complemented by a bibliometric analysis using VOSviewer to explore the relationship of terms, temporal trends, and concept density in the literature. The visualization results show that the terms "model" and "probability" are the main nodes in concept development, with the strengthening of the themes of distribution, uncertainty, and cross-disciplinary applications. The application of probability theory is seen dominantly in the fields of engineering, environment, transportation systems, and human behavior. The study also shows a shift in focus from classical risk distribution to more complex and contextual predictive modeling. The emergence of new terms such as "stack effect", "reaction time", and "p pod method" marks the growing interest in the application of probability in physical simulations and advanced technical systems. These results strengthen the position of probability theory as an adaptive conceptual framework in responding to the challenges of modern data analysis and uncertainty.